Characteristics of Rainfall Runoff and Soil Moisure Variation in Limestone Soil and Red Soil Slopes - CHEN Xiaona; PAN Yanfei; XU Qinxue; FANG Rongjie; WANG Shaoxu (Renmin Zhujiang)
This research investigates the characteristics of rainfall runoff and soil moisture variation in limestone soil and red soil slopes in the karst area of Northwest Guangxi. A self-made soil tank is utilized to simulate limestone soil and red soil slopes. The process of rainfall-runoff and soil moisture content of different depths of the soil layer (10 cm and 30 cm) are monitored under natural rainfall conditions, so as to compare and analyze the characteristics of different soil types in terms of rainfall runoff and soil moisture variation. The results are as follows. ① The runoff generation on limestone soil slopes is dominated by subsurface runoff, with an average subsurface runoff coefficient of 0.087; the runoff generation on red soil slopes is dominated by surface runoff, with an average surface runoff coefficient of 0.088. ② The runoff generation on limestone soil slopes starts only when the rainfall is moderate, and there is no significant change in the surface runoff coefficient with the increase of rainfall grade. The change of the coefficient of subsurgace runoff is complicated by the increase in rainfall level, with a down-up-down trend. The surface runoff coefficient of red soil slopes increases with higher rainfall levels; the runoff coefficient of subsurface runoff tends to decrease with increasing rainfall levels. ③ Under different rainfall levels, the runoff depth on limestone soil slopes is highly significantly correlated with the rainfall amount and rainfall duration, while the runoff on red soil slopes is highly significantly correlated with the rainfall duration. ④ The overall average soil moisture content of the limestone soil slopes (24.77%) is significantly lower than that of the red soil slopes (25.15%). The soil moisture content responds more rapidly to rainfall on the calcareous soil slopes than on the red soil slopes. The research results can provide a reference and reasonable opinions for the optimal allocation of precipitation resources on karst slopes.